2018
DOI: 10.1097/bsd.0000000000000665
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported Allergies are Associated With Preoperative Psychological Distress and Less Satisfying Patient Experience in a Lumbar Spine Surgery Population

Abstract: These findings highlight the potential utility of PRAs to help identify patients with psychological distress who are at risk for a poor experience of lumbar spine surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The association between HCAHPS-measured satisfaction and patient demographic and preoperative factors were investigated in three studies pertaining to spine surgical patients. [33][34][35][36] It was observed that allergies or depression in patients negatively impacted their reported satisfaction. 33,34 Specifically, Levin readmission.…”
Section: Press Ganeymentioning
confidence: 99%
See 2 more Smart Citations
“…The association between HCAHPS-measured satisfaction and patient demographic and preoperative factors were investigated in three studies pertaining to spine surgical patients. [33][34][35][36] It was observed that allergies or depression in patients negatively impacted their reported satisfaction. 33,34 Specifically, Levin readmission.…”
Section: Press Ganeymentioning
confidence: 99%
“…[33][34][35][36] It was observed that allergies or depression in patients negatively impacted their reported satisfaction. 33,34 Specifically, Levin readmission. 38 In another study of 391 lumbar spine surgery patients, longer post-operative length of stay was associated with lower top-box satisfaction for doctor listening and pain management subdivisions of the HCAHPS survey.…”
Section: Press Ganeymentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that the number of reported allergies is associated with both depression and anxiety in patients with lumbar spine disease. 8 On the contrary, the work of Xiong et al demonstrated that patient-reported allergies actually correlated with subjective improvement in pain and disability postoperatively. However, they found that this relationship did not persist longer than 1 year postoperatively, and they also found that a greater number of allergies corresponded with higher admissions costs and lengths of stay.…”
Section: Introductionmentioning
confidence: 98%
“…It has also been shown that the number of reported allergies is associated with both depression and anxiety in patients with lumbar spine disease. 8 …”
Section: Introductionmentioning
confidence: 99%